Deciphering The Complexity and Determinants of Malnourishment: A Locknow-Based Case-Control on Severe Acute Malnutrition - Verma, Deependra Kumar; N, Aishwarya; Singh, Vijay Kumar; Chandrakanta; Agarwal, Monica (Journal of Community Medicine and Public Health Research, 2025)
To identify risk factors for under-five children with malnutrition, the present study was conducted at two Nutritional Rehabilitation Centers (NRCs) in Uttar Pradesh, India, established to provide facility-based treatment for children affected by Severe Acute Malnutrition (SAM) and support for their mothers. A facilitybased case-control study was conducted in the Nutritional Rehabilitation centers of Barabanki and Lucknow district hospitals. The research covered all children admitted to these centers between July 1, 2018, and June 30, 2019, aged 1 to 59 months. A pre-tested, semi-structured questionnaire was filled out to collect information on various risk factors. The odds of a child belonging to the SAM category increased significantly if there was lack of toilet facility in the household, improper or absent water purification measures, failure to wash hands with soap and water after defecation, child is devoid of age-appropriate vaccination, has received pre-lacteal feeds, exclusively breast feed for less than 6 months and child was not a recipient of supplement from the Anganwadi Centre (AWC). Interventions within the health system are crucial for addressing the risk factors identified in the study. Since the strongest correlation was found with child feeding habits, programs to combat undernutrition should place a greater emphasis on nutritional education and counseling, as well as providing appropriate guidance.